The Analysis Relationship of Exclusive Breastfeeding with Psychosocial Problems in Children Aged 4-6 Years - Teuku Andi Syahputra; Asnawi Abdullah; Maidar Maidar; Fahmi Ichwansyah; Marthoenis Marthoenis (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2023)
Psychosocial health is one of the most important factors in achieving optimal growth and development in children. The increase in psychosocial problems among children has been accompanied by a decrease in the rate of exclusive breastfeeding over the past two years. Another important aspect is the history of natural disasters such as tsunamis, military operations, and the implementation of Islamic law in Aceh. This research aims to explore the relationship between exclusive breastfeeding and psychosocial problems in children in the city of Banda Aceh.The research method employed in this study is an analytical observational design with a cross-sectional approach. The population of this research comprises all children aged 4-6 years old. Samples were obtained using a cluster sampling technique, involving 296 children from 5 villages around one of the public health centers in Banda Aceh. Data analysis in this study is conducted using a logistic regression test.The results of the study indicate that the percentage of children aged 4-6 years in Banda Aceh who have received exclusive breastfeeding is 261 children (88.18%), while the number of children with psychosocial problems based on the Pediatric Symptom Checklist 17 is 27 children (9.12%). There is a significant relationship between exclusive breastfeeding and psychosocial problems in children aged 4-6 years in the working area of the Baiturrahman Public Health Center in Banda Aceh. Children who did not receive exclusive breastfeeding have a 5 times higher risk of experiencing psychosocial disorders compared to children who received exclusive breastfeeding during the first 6 months of life